persepsi pemberian kuis interaktif sebagai media evaluasi pembelajaran pada mahasiswa fakultas kedokteran - Lulu Rafika Putri (Yayasan Pendidikan Medika Indonesia, 2021)
Along with the rapid advancement of technology, the application of technology in the field of education, especially learning activities, is marked by the presence of e-learning or website-based learning that is beneficial for various parties who use it. The learning experience using website-based interactive quiz media has had an impact on primary and secondary education levels and is gradually being included in the scope of the University in response to the demand to understand the learning process of the younger generation and as a learning evaluation medium. In addition, the use of technology in education can be one way to improve the overall performance of higher education institutions.